2016
DOI: 10.3169/mta.4.227
|View full text |Cite
|
Sign up to set email alerts
|

[Invited Paper] Strategies for Searching Video Content with Text Queries or Video Examples

Abstract: (student member) †2 , Shicheng Xu (student member) †1 , Deyu Meng (member) †3 , Zexi Mao (member) †1 , Zhigang Ma (member) †1 , Ming Lin (member) †1 , Xuanchong Li (student member) †1 , Huan Li (member) †1 , Zhenzhong Lan (student member) †1 , Lu Jiang (student member) †1 , Alexander G. Hauptmann (member) †1 , Chuang Gan (student member) †4 , Xingzhong Du (student member) †5 , Xiaojun Chang (student member) †2Abstract The large number of user-generated videos uploaded on to the Internet everyday has led to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…They showed that deep features were more efficient for CBVR compared to other low-level features. Yu et al [26] also modified the architecture of 2D CNNs and utilized more data to improve the performance capabilities of existing 2D CNNs. Furthermore, they proposed a new feature fusion method to improve both the performance and robustness.…”
Section: A Use Of Cnns For Cbvrmentioning
confidence: 99%
“…They showed that deep features were more efficient for CBVR compared to other low-level features. Yu et al [26] also modified the architecture of 2D CNNs and utilized more data to improve the performance capabilities of existing 2D CNNs. Furthermore, they proposed a new feature fusion method to improve both the performance and robustness.…”
Section: A Use Of Cnns For Cbvrmentioning
confidence: 99%